PD‐1‐induced T cell exhaustion is controlled by a Drp1‐dependent mechanism. Issue 1 (14th October 2021) - Simula, Luca; Antonucci, Ylenia; Scarpelli, Giorgia; Cancila, Valeria; Colamatteo, Alessandra; Manni, Simona; De Angelis, Biagio; Quintarelli, Concetta; Procaccini, Claudio; Matarese, Giuseppe; Tripodo, Claudio; Campello, Silvia
Abstract : Programmed cell death‐1 (PD‐1) signaling downregulates the T‐cell response, promoting an exhausted state in tumor‐infiltrating T cells, through mostly unveiled molecular mechanisms. Dynamin‐related protein‐1 (Drp1)‐dependent mitochondrial fission plays a crucial role in sustaining T‐cell motility, proliferation, survival, and glycolytic engagement. Interestingly, such processes are exactly those inhibited by PD‐1 in tumor‐infiltrating T cells. Here, we show that PD‐1 pos CD8 + T cells infiltrating an MC38 (murine adenocarcinoma)‐derived murine tumor mass have a downregulated Drp1 activity and more elongated mitochondria compared with PD‐1 neg counterparts. Also, PD‐1 pos lymphocytic elements infiltrating a human colon cancer rarely express active Drp1. Mechanistically, PD‐1 signaling directly prevents mitochondrial fragmentation following T‐cell stimulation by downregulating Drp1 phosphorylation on Ser616, via regulation of the ERK1/2 and mTOR pathways. In addition, downregulation of Drp1 activity in tumor‐infiltrating PD‐1 pos CD8 + T cells seems to be a mechanism exploited by PD‐1 signaling to reduce motility and proliferation of these cells. Overall, our data indicate that the modulation of Drp1 activity in tumor‐infiltrating T cells may become a valuable target to ameliorate the anticancer immune response in future immunotherapy approaches. Abstract : PD‐1 signaling prevents TCR‐dependent Drp1 activation and subsequent mitochondrial fragmentation in T cells. In turn, this reduces both proliferation and migration of activated T cells. Cancer cells exploit this mechanism to downregulate T‐cell functionality within the tumor microenvironment, favoring tumor progression. These findings shed light on a new possible therapeutical approach for the treatment of solid cancers. (image made in BioRender).